اسهامات الفن التشكيلي الجزائري في مقاومة الاستعمار الفرنسي - بن عجمية, أمينة (كلية الأدب العربي والفنون, 2025)
لم يكن الاستعمار الفرنسي للجزائر مجرد احتلال عسكري بدأ عام 1830، بل كان نتيجة تخطيط مسبق ورغبة في السيطرة الثقافية والدينية والسياسية. استخدم الاستعمار شعارات مضللة كالتحديث والتحضر لفرض ثقافته ومحو الهوية الجزائرية في مختلف المجالات، من الدين والتعليم إلى الاقتصاد والمجتمع، مستهدفًا خاصة المرأة وصورة المجتمع العربي الإسلامي. ورغم استغلال الفن كأداة استشراقية، لم يكن الفنانون الجزائريون بعيدين عن المقاومة، فقد عبّروا بأعمالهم عن واقع شعبهم ومعاناته، فكان فنهم صوتًا صادقًا في وجه القمع. لقد تحوّل الفن إلى وسيلة للنضال وحفظ الذاكرة، وأسهم بدور رمزي وثقافي مهم في مسيرة التحرير الوطني.French colonialism in Algeria was not a military occupation; rather, it resulted from deliberate planning and a desire for cultural, religious, and political control. Colonialism used deceptive slogans such as modernization and civilization to impose its culture and destroy Algerian identity in various fields, from religion and education to the economy and society, particularly targeting women and the image of Arab-Islamic society. Despite using art as an Orientalist tool, Algerian artists were not far from resistance. Through their works, they expressed the reality and suffering of their people, and their art was an honest voice in the face of injustice. Art became a means of struggle and the preservation of memory, playing an important symbolic and cultural role in the process of national liberation.
Keywords: الاستعمار الفرنسي ،السيطرة الثقافية، محو الهوية الجزائرية ،الفنانون الجزائريون; French colonialism, cultural control, erasure of Algerian identity, Algerian artists‏